Analisis Erosi Tanah Akibat Alih Fungsi Lahan Hutan di Sub DAS Krueng Meuh Aceh - Nuraida; Zaki Yamani, Sayed Ahmad; Azhar, Rossy; Safitri, Amelia; Fahri, Zikri (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2024)
Erosion is the main problem that causes land degradation. Erosion causes many problems, such as reduced soil fertility and shallowing of reservoirs, loss of soil nutrients, environmental ecological damage, and decreased agricultural productivity. The Krueng Peusangan watershed has experienced land degradation through flooding, causing erosion. The flooding problem that occurs every year in the Krueng Peusangan watershed, especially in the Krueng Meuh sub-watershed, as a result of the conversion of forest land, impacts the community and the environment. The research aims to map the distribution of erosion areas in the Kreung Meuh Sub-watershed. The research method uses RUSLE spatial analysis. RUSLE analysis uses data on rain erosivity, soil erosivity, slope length, slope, and land use and conservation measures. The research results show that the Krueng Meuh sub-watershed has experienced erosion in light, medium, and heavy categories. Erosion is currently dominating the Krueng Meuh sub-watershed area, which has an area of 4,762.34 ha. Heavy erosion occurred on slopes >15% with an area of 1,675.27 ha. Meanwhile, very light erosion occurs on slopes <8% (flat) with forest land use with an area of 4,224.01 ha and 1,585.48 ha.